Clinical Observation of MRI Scanning Combined with Clinical Nursing for Surgical Breast Cancer Patients - Huan Zhang; Yanan Yin; Wenjing Tao; Ling Liu (International Journal of Analytical Chemistry)
The aim of this study was to explore the application effect of perioperative nursing care for patients with breast cancer. In this paper, 100 breast cancer patients with lymphatic spread treated by breast surgery in September 2019 to December were selected as the evaluation objects. They were divided into two groups according to preoperative imaging examination, 50 cases in each group. Group A was examined by B-ultrasound before axillary lymphadenectomy, group B was examined by MRI before axillary lymphadenectomy, and group C was examined by B-ultrasound and MRI before axillary lymphadenectomy. The facts in the three groups of disease findings were compared. Compared with the control group, the proportion of negative emotions (such as stress and depression) in the control group decreased (P<0.05). The decrease in blood cortisol was higher than in the control group (P<0.05). Improving the existing cancer surgery can improve the patient’s heart rate and reduce blood cortisol so as to improve the patient’s joint function and quality of life. The difficulty of nursing patients will also be reduced, which is medically necessary.